Fostering Student Engagement in Reading Class through Kinesthetic-Based Reading Race for Eighth Grade Students - Arinatus Safitri; Gusti Nur Hafifah; Nur Afifah (PROCEEDING UMSURABAYA, 2026)
This Classroom Action Research investigated the impact of a kinesthetic team-based Reading Race activity on multidimensional student engagement among eighth-grade English as a Foreign Language (EFL) learners in an Indonesian junior high school. Focusing on five dimensions of engagement—enthusiasm, physical engagement, teamwork, text comprehension, and self-regulation (confidence and discipline), the study used classroom observations and a 20-item Likert-scale questionnaire to collect data before and after one intervention cycle consisting of two meetings. Quantitative analysis revealed high levels of engagement across all dimensions, with teamwork and physical engagement scoring the highest. Qualitative observations supported these findings, highlighting active participation, collaboration, and increased motivation during the kinesthetic reading task. While text comprehension and self-regulation showed positive improvements, both also indicated areas for further development. The study concluded that the Reading Race method effectively fostered holistic engagement in EFL classrooms by integrating movement, competition, and cooperative learning. The findings offer practical insights for educators seeking to accommodate diverse learning styles and improve reading instruction in Indonesian junior high schools.